If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(6 + -1x) + 15 = -51 (6 * -6 + -1x * -6) + 15 = -51 (-36 + 6x) + 15 = -51 Reorder the terms: -36 + 15 + 6x = -51 Combine like terms: -36 + 15 = -21 -21 + 6x = -51 Solving -21 + 6x = -51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 6x = -51 + 21 Combine like terms: -21 + 21 = 0 0 + 6x = -51 + 21 6x = -51 + 21 Combine like terms: -51 + 21 = -30 6x = -30 Divide each side by '6'. x = -5 Simplifying x = -5
| 5c+6=-4+4(c+8) | | 18x+53=7x-68 | | 2G-9=5 | | 7t-18=-16 | | 48=12+6n | | 8x-1=-3x+21 | | x^2+40=12x | | -4m+3=9 | | -4x+15=-45 | | 7(1-3x)+8x=98 | | 4(3x-8)=10 | | (x-7)2.3=4 | | 3n-8n-6=12 | | 10-4x=54 | | 8ln(x+8)-2lnx= | | Y+10=9y-33 | | 127x-100=7x | | 4x-7(1x-4)=6 | | m+10=10 | | -3(x-4)=x-7 | | 5=2y-1 | | 2x=(300/4) | | -4(7a-3)=-3a+37 | | 3x-8=3x | | 22+31x=177 | | 5y-7+3x+2=180 | | r-17m-8=3(2r-4m)-5(m+3-r) | | 22+31=177 | | x-4=6x+11 | | 8*1-4y=12 | | 36b=90 | | 6x+6=-6 |